Infectious diseases and arthropods - Goddard, Jerome (Totowa, N.J. : Humana Press, 2008)
Summarizes the biological, entomological, and clinical aspects of mosquito-, tick-, and flea-borne diseases, and a variety of other miscellaneous vector-borne diseases. The book provides for each disease a description of the vector involved, notes on its biology and ecology, distribution maps, and general clinical guidelines for treatment and control.--From publisher's description.
Section I. Arthropods and human health -- 1. Arthropods and health -- 1.1. Classification of arthropods -- 1.2. Medical importance of arthropods -- 2. Dynamics of arthropod-based diseases -- 2.1. Mechanical vs biological transmission of pathogens -- 2.2. Vector competence -- Section II. Major arthropod-borne diseases -- 3. Mosquito-borne diseases -- 3.1. Basic mosquito biology -- 3.2. Malaria -- 3.3. Mosquito-transmitted encephalitis viruses -- 3.4. Dengue fever -- 3.5. Yellow fever (YF) -- 3.6. Lymphatic filariasis -- 3.7. Other human-infesting filarial worms -- 4. Tick-borne diseases -- 4.1. Basic tick biology -- 4.2. Rocky Mountain-spotted fever (RMSF) -- 4.3. American boutonneuse fever (ABF) -- 4.4. Other spotted fever group rickettsioses -- 4.5. Ehrlichiosis -- 4.6. Lyme disease -- 4.7. Tularemia -- 4.8. Human babesiosis -- 4.9. Viruses transmitted by ticks -- 4.10. Tick-borne relapsing fever (TBRF) -- 4.11. Tick paralysis -- 5. Flea-borne diseases -- 5.1. Basic flea biology -- 5.2. Plague -- 5.3. Murine typhus -- 5.4. Cat-scratch disease (CSD) -- 6. Sand fly-transmitted diseases -- 6.1. Basic sand fly biology -- 6.2. Leishmaniasis -- 6.3. Other sand fly-transmitted diseases -- 7. Miscellaneous vector-borne diseases -- 7.1. Chagas' disease -- 7.2. African sleeping sickness -- 7.3. Onchocerciasis -- 7.4. Scrub typhus (ST) -- 7.5. Louse-borne infections -- 8. Bed bugs -- 8.1. Introduction to bed bug biology -- 8.2. Bed bugs and disease transmission -- 9. Why mosquitoes and other arthropods cannot transmit HIV -- Section III. Other arthropod-caused or -related problems -- 10. Brown recluse bites: facts and fables -- 10.1. Introduction and biology -- 10.2. Facts and fables about brown recluse bites -- 10.3. Differential diagnosis -- 10.4. Treatment of bites -- 11. Fire ant attacks on humans -- 11.1. The problem -- 11.2. Effects of the venom -- 11.3. Infectious complications -- 11.4. Protecting patients in health care facilities from ant attacks -- 12. Medical conditions caused by arthropod stings or bites -- 12.1. Introduction and medical significance -- 12.2. Pathogenesis -- 12.3. Clues to recognizing insect bites or stings -- 12.4. Summary and conclusions -- 13. Myiasis -- 13.1. Introduction and medical significance -- 13.2. Contributing factors -- 13.3. Prevention, treatment, and control -- 14. Imaginary insect or mite infestations -- 14.1. Introduction and medical significance -- 14.2. Clinical aspects and contributing factors -- 14.3. Differential diagnosis -- 14.4. Treatment strategies -- Appendix 1. Signs and symptoms of arthropod-borne diseases -- Appendix 2. Diagnostic tests used in arthropod-borne diseases.
Includes bibliographical references and index.
Keywords: Arthropod vectors; Arboviruses; Protozoan diseases; Infection; Arthropod Vectors; Arbovirus Infections; Protozoan Infections; Arboviruses; Arthropod vectors; Infection; Protozoan diseases